2014
DOI: 10.3897/zookeys.437.7917
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and systematics of the westernmost Italian Dolichopoda species (Orthoptera, Rhaphidophoridae)

Abstract: The genus Dolichopoda (Orthoptera; Rhaphidopohoridae) is present in Italy with 9 species distributed from northwestern Italy (Piedmont and Liguria) to the southernmost Apennines (Calabria), occurring also in the Tyrrhenian coastal areas and in Sardinia. Three morphologically very close taxa have been described in Piedmont and Liguria, i.e., D. ligustica ligustica, D. ligustica septentrionalis and D. azami azami.To investigate the delimitation of the northwestern species of Dolichopoda, we performed both morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…All the haplogroups are geographically distributed with a resulting scenario rather heterogeneous. Pairwise comparisons between the Peloponnesian species range between 2.5% and 8.3%, falling in the range of interspecific comparisons observed in all the other studied Dolichopoda species (Figure 3, Allegrucci et al, 2014) and consistent with divergence values found in other insect species (see for…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All the haplogroups are geographically distributed with a resulting scenario rather heterogeneous. Pairwise comparisons between the Peloponnesian species range between 2.5% and 8.3%, falling in the range of interspecific comparisons observed in all the other studied Dolichopoda species (Figure 3, Allegrucci et al, 2014) and consistent with divergence values found in other insect species (see for…”
Section: Discussionsupporting
confidence: 84%
“…To investigate this further we carried out a genetic distance analysis using the COI gene as a barcode and p distance between all studied Dolichopoda species (Allegrucci et al 2005(Allegrucci et al , 2009(Allegrucci et al , 2011(Allegrucci et al , 2014Martinsen et al 2009). Genetic distance values at intra-and interspecific levels are compared in Figure 3.…”
Section: Genetic Distances and Species Delimitationmentioning
confidence: 99%
“…Furthermore these species show significant variation in life history and ecological traits. The cave cricket Dolichopoda laetitiae is generally abundant in subterranean environments of Central Italy ( Allegrucci et al, 2014 ). These crickets are scavengers of subterranean environments but can also feed outside caves, thus increasing the supply of allochthonous organic matter into the caves ( Lavoie, Helf & Poulson, 2007 ; Weckerly, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was successfully extracted from the tissue samples using the GenElute™ Tissue Genomic DNA Purification Kit (Sigma Aldrich, St. Louis, MO, USA), following the same protocol as in the previous papers (Allegrucci et al., , , , ). Three mitochondrial DNA fragments ( COI , 12S rRNA, and 16S rRNA ) and two nuclear ones ( 18S rRNA and 28S rRNA ) were amplified and sequenced.…”
Section: Methodsmentioning
confidence: 99%